2016
DOI: 10.1038/cgt.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

Retargeted adenoviruses for radiation-guided gene delivery

Abstract: The combination of radiation with radiosensitizing gene delivery or oncolytic viruses promises to provide an advantage to improve therapeutic results in glioblastoma. X-rays can induce significant molecular changes in cancer cells. We isolated the GIRLRG peptide that binds to radiation-inducible 78-kDa glucose-regulated protein (GRP78), which is overexpressed on the plasma membranes of irradiated cancer cells and tumor-associated microvascular endothelial cells. The goal of our study was to improve tumor-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…There has been considerable preclinical studies supporting expression of a variety of genes that help promote cytotoxic killing of tumor cells, induction of immune responses, inhibition of tumor neoangiogenesis, enhancing radiosensitization and other strategies. [8][9][10] Other considerations in OV development includes selection of how to deliver the virus to the patient with cancer and, while initial studies used direct intratumoral (IT) injections, this may be logistically challenging for visceral and central nervous system (CNS) tumors. Other strategies have included intravenous administration which is logistically simple and allows targeting of multiple metastatic lesions but may be complicated by rapid dilution in the circulation, neutralization by antiviral antibodies and other serum proteins, and ultimately limited biodistribution to tumors.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable preclinical studies supporting expression of a variety of genes that help promote cytotoxic killing of tumor cells, induction of immune responses, inhibition of tumor neoangiogenesis, enhancing radiosensitization and other strategies. [8][9][10] Other considerations in OV development includes selection of how to deliver the virus to the patient with cancer and, while initial studies used direct intratumoral (IT) injections, this may be logistically challenging for visceral and central nervous system (CNS) tumors. Other strategies have included intravenous administration which is logistically simple and allows targeting of multiple metastatic lesions but may be complicated by rapid dilution in the circulation, neutralization by antiviral antibodies and other serum proteins, and ultimately limited biodistribution to tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 60 Ionizing radiation is known to upregulate multiple endocytosis pathways as well as increase surface antigens and receptors that could potentially facilitate endocytosis of AMONs. 24 , 61 The cell membrane lipid bilayer is naturally impermeable to complexes >1 kDa, alternate strategies involving the modulation of endocytosis using lipid-based drug delivery systems, nanoscale carriers and synthetic receptor targeting adapted for high affinity binding of targeting molecules and clathrin-dependent uptake are not novel and some of these are currently being evaluated in clinical trials. 62 , 63 , 64 Radiation-mediated enhanced intracellular uptake as well as microbubble oscillation using ultrasound to deliver adeno-viral vectors, plasmid DNA or siRNA have been previously described by upregulation of the physiological endocytosis pathways and our study for the first time demonstrate the use of a priming dose of non-ablative ionizing radiation-enhanced delivery of unmodified morpholino oligomers to effectively knockdown target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is a common therapeutic choice for lung adenocarcinoma ( 4 ). Gene-radiotherapy, the combination of traditional radiation and targeted gene therapy is a recent breakthrough in cancer treatment ( 22 ). In a previous study, proteomic analysis of pulmonary adenocarcinoma demonstrated an upregulation of CyPA following radiotherapy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%